Transformer collectivement et localement le service public des déchets : expérimentations dans des tiers-lieux-ressourceries franciliennes - Marion Boespflug; Thomas Lamarche (Développement Durable et Territoires, 2022)
In a bottom-up dynamic and at a local level, third sector organisations develop services promoting the reuse and repair of second-hand objects. They are seen as an alternative to the dominant model and often involve the exploration of collective governance. New operators are joining the public service, generating new types of interaction with it. Among these projects, third places are emerging in the form of second-hand shops, or « ressourceries », creating experimental and hybrid models of them. This article explores the contributions of their experimentations in the « ressourcerie » activity. It also reviews the experimentation processes and the place that third places take in them.